Substantiation of the Design and Layout Scheme for the Gravity-Pneumatic Soybean Seed Cleaner - V. G. Khamuev; S. A. Gerasimenko (Сельскохозяйственные машины и технологии)
It is shown that scientifi c research into the intensifi cation of soybean seed separation processes is necessary for developing new type purifi cation technologies that eliminate the shortcomings of traditional machines, as well as achieving more favorable technical and economic indicators of grain cleaning equipment. (Research purpose) To substantiate the design parameters of a cleaning and sorting plant for highly efficient separation of soybean seeds. (Materials and methods) We used a developed prototype model of the plant for cleaning soybean seeds, consisting of a gravity column and a pneumatic cleaning and sorting channel. The number of combs in the gravity column and the gap between the comb bars were substantiated. Subject to different supply of material, the completeness of separating a large impurity was determined in a gravity column, a light impurity – in the first section of the channel, soybean halves – in the second section of the channel, small and puny soybean seeds – in the third one. (Results and discussion) The optimal number of combs for the gravity column was set to 10 pieces with a gap between the comb bars of 10 millimeters, thus providing the separation effi ciency of 99.3 percent. It was obtained that the optimal ratio between the width of the narrowing partition and the 50-millimeters depth of the channel section equals 0.37. The width of the narrowing partitions was calculated to be 55.5 millimeters; the optimal supply of soybeans is 2.5 tons per hour, thus providing the separation completeness in the gravity column of no less than 95 percent, and that in the pneumatic channel of no less than 98 percent. (Conclusions) It was determined that the intensifi cation of the soybean seed separation process is possible by the combined use of a gravity column and a pneumatic separating device, which can increase the productivity and effi ciency of soybean cleaning by 20 percent or more.